Peran Pendidikan Keluarga Yang Harmonis dan Yang Berkarakter Islami Terhadap Pembentukan Kepribadian Pada Anak Usia Dini di Desa Kramat Mengare Bungah Gresik - Ainiyah, Maslakhatul (Jurnal Studi Multidisiplin Qomaruna, 2023)
A harmonious family is a stable family with minimal conflict, serving as the first and most important educational institution for children. In shaping a child's personality, the family plays a crucial role as the initial foundation. Therefore, the roles of both parents are important in shaping the direction and tone of the family, especially since children are not yet able to be responsible for themselves and are highly dependent on their parents in various aspects, from physical needs to life perspectives. This study aims to describe the extent to which harmonious and Islamic-character family education plays a role in shaping the personality of young children. Using a descriptive qualitative approach through observation and interviews in Desa Kramat, Mengare, Gresik, it was found that community awareness of early childhood education is quite good, especially among those with a decent socio-economic status. This indicates that a harmonious family and strong religious education contribute significantly to the formation of a child's personality, particularly in the context of coastal communities like Desa Kramat.